Analiza procesów magazynowania biowodoru jako paliwa - Krzysztof Biernat; Sylwia Gołębiowska (Studia Ecologiae et Bioethicae)
Possibilities of biohydrogen fuel storing were represented. Hydrogen can be store in gas, liquid, or constant form. Technological, material, and economic hydrogen storing determinates were shown. Experiments and researches on finding optimal hydrogen storage methods have been taken into consideration.